(untitled) (Società e diritti, 2025)
The paper focuses attention on the fact that in a multicultural and multiethnic society, in which victimization and cultural violence towards foreigners is increasingly evident, a decisive action to recover the humanitarian component is absolutely necessary, especially in the healthcare context and cultural. Therefore, empathic doctor-foreign patient communication is a priority in order to understand the patient’s personal experience and cultural background. In full respect of the foreigner as a person, it is necessary to promote a careful and widespread educational work to train competent cultural mediators, filter figures between the migrant and the society in which he is inserted and able to exactly decode the intercultural communication between doctor and foreign patient. Particular attention then deserves in the healthcare context the foreign woman, who often experiences a situation of isolation, discomfort, vulnerability in the new country and who finds herself in a condition of subordination compared to man.